SIMULATION MODELS OF RESISTANCE TO CONCRETE MOVEMENT IN THE CONCRETE CONVEYING PIPE OF THE AUTOCONCRETE PUMP - Anofriev, P. G. (Science and Transport Progress, 2015)
Purpose. In modern construction the placing of concrete is often performed using distribution equipment of concrete pumps. Increase of productivity and quality of this construction work requires improvement of both concrete pumps and their tooling. The concrete pumps tooling consists of standardized concrete conveying pipes and connector bends radius of up to 2 m. A promising direction of tooling improvement is the reduce of resistance to movement of the concrete in the concrete conveying pipe by increasing the radius of the bend. The aim of this study is to determine the feasibility of developing and implementing connector bends with radius greater than 2 m. Methodology. The criterion of efficiency in using bends with radius of more than 2 m in connector concrete pipes is reduction of resistance to movement of the concrete, enhancing the productivity of concrete pumps. Studies of resistance to movement of concrete in the concrete conveying pipe are performed on the mathematical simulations. Findings. On the proposed models are calculated the resistance to movement of concrete in the concrete conveying pipe of the autoconcrete pump with a three-section distribution boom. Reduction of the resistance to concrete movement was obtained for the four major sections of the provisions of the distribution boom in the autoconcrete pump. Originality. Two mathematical simulations were developed to calculate the resistivity to concrete movement in the bends of concrete conveying pipe depending on the radius of the bend. Practical value. The proposed by the author simulations allow us to calculate resistivity to the concrete movement in the concrete conveying pipe and general resistance to the concrete movement in the concrete pipe of the autoconcrete pump with three sections of the distribution boom. The study found a decrease of 10.3−75.5% of the resistance to concrete movement in the concrete conveying pipe with connector bends of an increased radius. These results confirm the usefulness of the bends application in the concrete conveying pipe with a radius of more than 2 m.